POTENTIAL USE OF FENNEL (FOENICULUM VULGARE) AS FISH IMMUNOSTIMULANT: ARTICLE REVIEW - Rangga Idris Affandi; Damai Diniariwisan (Jurnal Perikanan Unram, 2024)
The development of aquaculture systems from traditional to intensive has the potential to increase environmental pollution and other problems such as the emergence of disease. One of the fish health management that can be applied to control disease attacks is by taking action to prevent fish disease by administering immunostimulants. Sources of natural immunostimulants can come from plants. Ingredients in natural plants can be immunostimulants for fish, one of which is the fennel (Foeniculum vulgare). Fennel is generally known as a raw material for making bitter herbal medicine which has many benefits for the human body because of its content. Therefore, the aim of this literature review research is to provide a clear picture of the potential of the fennel as an immunostimulant in fish. The method used is a systematic literature review with stages of taking data from the library, then continuing with reading, taking notes and processing research material from articles resulting from research on the potential of fennel as an immunostimulant in fish. The results showed that fennel contain various bioactive compounds with the largest content being flavonoids which can be used as immunostimulants in aquaculture. Fennel have great potential for further research development in an effort to make this material an immunostimulant in large-scale aquaculture.